Recruitment of focal adhesion kinase and paxillin to β1 integrin promotes cancer cell migration via mitogen activated protein kinase activation - Crowe, David L (BioMed Central, 2004)
BACKGROUND: Integrin-extracellular matrix interactions activate signaling cascades such as mitogen activated protein kinases (MAPK). Integrin binding to extracellular matrix increases tyrosine phosphorylation of focal adhesion kinase (FAK). Inhibition of FAK activity by expression of its carboxyl terminus decreases cell motility, and cells from FAK deficient mice also show reduced migration. Paxillin is a focal adhesion protein which is also phosphorylated on tyrosine. FAK recruitment of paxillin to the cell membrane correlates with Shc phosphorylation and activation of MAPK. Decreased FAK expression inhibits papilloma formation in a mouse skin carcinogenesis model. We previously demonstrated that MAPK activation was required for growth factor induced in vitro migration and invasion by human squamous cell carcinoma (SCC) lines. METHODS: Adapter protein recruitment to integrin subunits was examined by co-immunoprecipitation in SCC cells attached to type IV collagen or plastic. Stable clones overexpressing FAK or paxillin were created using the lipofection technique. Modified Boyden chambers were used for invasion assays. RESULTS: In the present study, we showed that FAK and paxillin but not Shc are recruited to the β1 integrin cytoplasmic domain following attachment of SCC cells to type IV collagen. Overexpression of either FAK or paxillin stimulated cancer cell migration on type IV collagen and invasion through reconstituted basement membrane which was dependent on MAPK activity. CONCLUSIONS: We concluded that recruitment of focal adhesion kinase and paxillin to β1 integrin promoted cancer cell migration via the mitogen activated protein kinase pathway.